Web Based Procurement Information System Design ( case study: PT. Restindo Dayatama ) - yusup kurniawan; Jejen Jaenudin; Safaruddin H. Al Ikhsan (Jurnal Mantik, 2021)
PT. Restindo Dayatama is a manufacturer company engaged in the car body industry which concentrates on seat products, especially bus seats. PT.Restindo Dayatama in procuring goods cannot be separated from computerization. When the stock of goods in the warehouse runs out, the warehouse clerk submits a request for goods to the procurement by providing a letter of request for goods made through Microsoft Excel. This process is constrained by efficiency, and there is often duplication of data on demand for goods which results in goods piling up in warehouses. Therefore, PT. Restindo Dayatama requires a procurement information system that can assist in carrying out procurement transactions, calculating and storing more data, accessing data faster and making time more efficient. The development method uses DFD (Data Flow Diagram) and system development that will be built using a waterfall so as to produce a procurement information system.